Inventário de sete edificações em alvenaria de tijolo na zona rural de Silveira Martins- RS - Thies, Cristiane Leticia Oppermann (2018)
The valuation of cultural heritage makes it possible for a community to come into contact with its history. The built material patrimony is one of the most visible ways of maintaining points of recognition and understanding of the past history. Through measures like the inventory of buildings it is possible that the buildings are registered and valued. The region of Silveira Martins has a large built heritage of buildings from the time of the arrival of Italian immigrants, mostly in brick. In order to preserve part of this patrimony, the present study is an inventory of houses built in brick and without plastering in the rural area of Silveira Martins-RS in the period between 1877 and 1930. Seven buildings were inventoried, with the characteristics mentioned above and which will be compared to the lower floors of Italian houses in the Veneto and Belluno region of Italy, to see if they follow the same spatial configurations. For the cataloging of the buildings were used the inventory sheets used by IPHAE and the selection criteria were the construction typology and the absence of plastering to facilitate the visualization of the construction details. Bibliographic review, survey of buildings, measurements and redesign were carried out for subsequent analysis and interpretation and comparison of the results with the literature data. From these analyzes were made inventory records to record the results. As a conclusion, it is necessary to value and raise public awareness about this great built heritage that can contribute significantly to the development of the region